Comparison of three methods for teaching mechanical ventilation in an emergency setting to sixth-year medical students: a randomized trial - Tallo,Fernando Sabia (2020)
SUMMARY OBJECTIVE: To determine if there are significant differences between the tutorial, simulation, or clinical-case-based discussion teaching methods regarding the transmission of medical knowledge on mechanical ventilation. METHODS: A randomized, multicenter, open-label controlled trial was carried out using 3 teaching methods on mechanical ventilation: clinical-case-based discussion, simulation, and online tutorial. Voluntary students of the sixth year of medical school from 11 medical colleges answered a validated questionnaire on knowledge about mechanical ventilation for medical students before, immediately after, and 6 months after in-person training consisting of 20 multiple-choice questions, and 5 questions about the participants' demographic profile. RESULTS: Immediately after the test there was no difference between the scores in the simulation and clinical case groups,[15,06 vs 14,63] whereas, after some time, there was a significant difference in retention between the case-based and simulation groups, with the score in the simulation group 1.46 [1.31; 1.64] times higher than the score of the case group (p-value < 0.001). In the multivariate analysis, an individual who had received more than 4 hours of information showed an increase of 20.0% [09.0%; 33.0%] in the score (p-value = 0.001). CONCLUSIONS: Our results indicate that, in comparison with other forms of training, simulation in mechanical ventilation provides long-lasting knowledge in the medium term. Further studies are needed to improve the designing and evaluation of training that provides minimal mechanical ventilation skills.